Subjective Well-Being dan Komitmen Organisasi Pada Karyawan yang Menjalani Work From Office (WFO) di Masa Pandemi - Lidia Kastanya; Stevina Cuangganatha (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
This studi aims to learn the correlation between subjective wellbeing and organization commitment of employees work from office (WFO) during the pandemic covid-19. This research uses quantitative approach. The subjexts of this atudy were 82 employees who worked in Jakarta area. Data collection methods usea are the scale of Organizational Commitment Questionnaire (OCQ) and scale subjective wellbeing Satisfaction with Life (SWLS) and Scale of Positive and Negative Experience (SPANE). Data analysis techniques used Pearson’s Correlation Product Moment. The results of the study using the pearson product moment the showed that the correlation test value formed was 0,318 and sig 0.004, where this number indicated a positive and significant correlation between the organizational commitment vaviable with subjective wellbeing meaning the highers subjective wellbeing, the higher commitment to organizational. Penelitian ini bertujuan untuk mengetahui hubungan subjectve wellbeing dengan komitmen organisasi pada karyawan yang menjalani work from office (WFO) di masa pandemi COVID-19. Penelitian ini menggunakan pendekatan kuantitatif. Subjek penelitian 82 karyawan yang bekerja di area jakarta. Metode pengumpulan data yang digunakan adalah skala komitmen organisasi Organizational Commitment Questionnaire (OCQ) dan skala subjective wellbeing Satisfaction with Life (SWLS) dan Scale of Positive and Negative Experience (SPANE). Teknik analisa data menggunakan Pearson’s Correlation Product Moment. Hasil penelitian menggunakan uji korelasi preason product momen menunjukan bahwa nilai uji korelasi yang terbentuk adalah sebesar 0,318 dan sig 0.004, dimana angka ini menunjukan korelasi yang positif dan signifikan antara variabel komitmen organisasi dengan subjective wellbeing, artinya semakin tinggi subjectivewell being yang dimiliki, maka semakin tinggi juga komitmen kepada organisasi yang dimiliki karyawan.